The Proportional Relationship in The Three-Aisle Basilicas in Constantinople, Cilicia, Lycian, Lidia and Caria Regions (4th-6th Centuries) - Sinan Yılmaz; Cahit Karakök (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
With the emergence and spread of Christianity, many basilicas were built in Anatolia. The early period basilicas were generally designed in the same form by the masters of the period. There are no pastophorium cells in these basilicas. They usually appear as structures with a simple rectangular narthex. Our main problem is to evaluate these basilicas from a mathematical point of view. At the beginning of the questions to be asked about these basilicas, did every master apply the mathematical operation exactly? Did the masters build these structures by continuing the traditional method or did they do it with a good knowledge of mathematics? What kind of differences do basilicas built from region to region? This study, which we have discussed, asks the question of the effectiveness of traditional methods as well as mathematical methods when building basilicas. The question of whether architects adhere to mathematical methods and how important traditional methods can be for them is emphasized. Moreover, our study deals with how the early period basilicas are proportionally related. At this point, the churches were determined and the results were obtained.